2015
DOI: 10.1515/cerce-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydro-Priming on Germination Characteristics, Seedling Growth and Antioxidant Activity of Accelerated Aging Wheat Seeds

Abstract: Seed aging is an important problem in developing countries which seeds stored in inappropriate condition. Delayed germination, reduced normal seedling percentage and changed antioxidant enzymes activity are some indications of aged seeds. Priming is a technique applied before planting and can improve seed characteristics especially under abiotic stress conditions. The main objective of the study was to evaluate aging effect on seed quality and to study the interaction between seed aging and seed priming. A fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…SDW values were found significantly reduced with the increased period of accelerated aging in case of both the crops. This result was in accordance for wheat seeds (Ghasemi et al 2014).…”
Section: Seedling Dry Weight (Sdw)supporting
confidence: 89%
“…SDW values were found significantly reduced with the increased period of accelerated aging in case of both the crops. This result was in accordance for wheat seeds (Ghasemi et al 2014).…”
Section: Seedling Dry Weight (Sdw)supporting
confidence: 89%
“…The enzyme causes increased metabolic activity, radical cell elongation, and subsequent growth (Fitri, 2015). It is suspected that soaking provides sufficient water for transport within the plant body, the results of research by Ghasemi et al (2014) showed that soaking for 24 hours had a significant effect on shoot height compared to controls that were not soaked.…”
Section: Height Of a Shallot Plantmentioning
confidence: 99%
“…Sowing of wheat on 22 nd of November with 16 hours hydro-primed seeds resulted highest germination, growth, yield parameters as well as highest economic return (Patra et al, 2016;Sitanshu et al, 2017). Hydro priming of wheat seeds also helped to improve the aged wheat seeds quality, induced increment in enzyme activity, improved germination and seedling characteristics (Ghasemi et al, 2015).…”
Section: Wheatmentioning
confidence: 99%